THE EFFECT OF DEBT AND DIVIDEND POLICY ON FIRM VALUE MODERATED BY MANAGERIAL OWNERSHIP: ( Case Study of Manufacturing Companies Listed on the Indonesia Stock Exchange) - Anggi, Anggi; Taswan, Taswan (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: The objective of this study is to investigate the effect of debt policy and dividend policy on company value, moderated by managerial ownership, among groups listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Methods: The unbiased variables analyzed in this study are debt coverage and dividend coverage, while the dependent variable is organisational price. Managerial possession serves as a moderating variable.The population in this study comprises manufacturing businesses listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Results: A total of sixty-four groups have been determined as samples using purposive sampling. The consequences of the examination indicate that Debt policy has a significant and widespread impact on firm cash, while Dividend insurance has a significant effect on firm fees. Managerial possession has a nice impact on the company's fee. Managerial ownership moderates the connection between debt coverage and company cost. Managerial ownership also moderates the relationship between dividend policy and a company's stock price. Keywords: Debt Policy, Managerial Ownership, Dividends, Firm Value